Megafaunal Community Structure From the Abyssal to Hadal Zone in the Yap Trench - Zhang, Dongsheng; Zhou, Yadong; Yang, Jichao; Linley, Thomas; Zhang, Ruiyan; Lu, Bo; Xu, Peng; Shen, Chengcheng; Lin, Shiquan; Wang, Yueyun; Sun, Dong; Wang, Xiaogu; et al. (Frontiers in Marine Science, 2021)
Hadal trenches remain one of the unexplored ocean ecosystems due to the challenges of sampling at great depths. It is still unclear how a faunal community changes from the abyssal to the hadal zone, and which environmental variables are the key impacting factors. In this study, nine dives of the Human Occupied Vehicle (HOV) “JIAOLONG” were conducted from abyssal to hadal zonedepths (4435–6796 m) in the Yap Trench on the southeastern boundary of the Philippine Sea Plate in the western Pacific, divided into 48 200m video transects, to describe the megafaunal communities and reveal their relationship with environmental factors. A total of 1171 megafauna organisms were was recorded, 80 morph-ospecies (msps) from eight phyla were identified based on the video data, most of which were reported for the first time in the Yap Trench. Arthropoda was the most abundant phylum and Echinodermata was the most diversified diverse phylum of the megafaunal community. The faunal abundance increased with depth whereas the Shannon diversity index decreased with depth. Cluster analysis suggested seven assemblages, with five abyssal groups, one mixed group, and one hadal dominant group. Although Mmegafaunal communities changed gradually from abyssal zone to hadal zone, both PERMANOVA and PERMDISP analysis analyses revealed that the communitiesy are significantly different between abyssal zone and hadal zone, indicating 6000 m as the boundary between the two depth zones. Depth, substrate, slope, and latitude were identified as four important environmental factors with significant influence on megafaunal community structure. This study proposed a transition pattern from the abyssal to hadal zone in the Yap Trench, highlighted the importance of habitat heterogeneity in structuring megafaunal community in a hadal trench.